2017
DOI: 10.1186/s13099-017-0222-9
|View full text |Cite
|
Sign up to set email alerts
|

Low distribution of genes encoding virulence factors in Shigella flexneri serotypes 1b clinical isolates from eastern Chinese populations

Abstract: BackgroundThe ability of Shigella to invade, colonize, and eventually kill host cells is influenced by many virulence factors. However, there is no analysis of related genes in Jiangsu Province of China so far. Shigella flexneri was collected from 13 cities of Jiangsu Province through the provincial Centers for Disease Control (CDC) for analysis of distribution of major virulence genes (ipaH, ipaBCD, ial, virF, virB, sigA, set1A, sepA, sat, pic, set1B and sen) detected by PCR technology.ResultsA total of 545 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 42 publications
(45 reference statements)
12
18
1
Order By: Relevance
“…Subsequently, the invE protein reverses the H-NS induced inhibition of transcription, which eventually elicits virulence genes on the plasmid. 3,22 In our study, both virF and invE were found in (84.6%) of EIEC isolates. These results are approximately consistent with the previous study.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Subsequently, the invE protein reverses the H-NS induced inhibition of transcription, which eventually elicits virulence genes on the plasmid. 3,22 In our study, both virF and invE were found in (84.6%) of EIEC isolates. These results are approximately consistent with the previous study.…”
Section: Discussionsupporting
confidence: 51%
“…Of 13 strains of EIEC, 84.6% (n=11) isolated from children under the age of 2 years (P<0.05). Children were categorized into five different groups according to their age: (0-12), (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), (35-48), and (49-60) months. Distribution of EIEC strains according to age, gender, and clinical symptoms are shown in Table 3.…”
Section: Distribution Of Eiecmentioning
confidence: 99%
“…5 Shigellosis is caused by the members of shigella species including Shigella dysenteriae, Shigella flexneri, Shigella sonnei, and Shigella boydii. 6 S. dysenteriae and S. flexneri are principally responsible for epidemic and endemic shigellosis, respectively, with high transmission rates and significant mortality rates in low-income countries whereas S. sonnei and S. boydii generally cause a relatively mild self-limiting watery diarrhea. 7 The ability of shigella spp.…”
Section: Introductionmentioning
confidence: 99%
“…Hossain et al 2018); afimbrial adhesion factors (sfa) for E. coli(Rahdar et al 2015); the UDP galacturonate 4-epimerase (uge) gene for Klebsiella pneumoniae (Regu e et al 2004); nitric oxide reductase (norB) and thioredoxin (trx) genes for Flavobacterium columnare (Zhang and Arias 2009); enterotoxin A (toxA) for Pseudomonas aeruginosa(Ertugrul et al 2018); invasion plasmid antigen H (ipaH) and shiga-toxin (sigA) genes for Shigella sp (Thiem et al 2004;Fan et al 2017)(Terao 2012); and…”
mentioning
confidence: 99%